The quadratic formula is above.
You want each equation in standard form: ax^2 + bx + c = 0
I begin each problem by defining variables.
For instance 3. Is in standard form. X^2 -2x - 3 = 0. a = 1, b = -2, c = -3
Now use quadratic formula: x = [- b + or - sqrt(b^2 - 4ac)]\2a
Answer:
B
Step-by-step explanation:
The exponential function has the form
where a is the starting value or y-intercept. B is the rate of change and x is the variable typically time. In this situation,
has starting value 4, rate 3 and a -x.
Normally an exponential curve glides left to right growing steeper as it goes. But a -x flips this behavior. The curve starts very steep then gradually slows down. This means only graphs B or D are options. Since only graph B of these two has a y-intercept at 4, graph B is the solution.
825/3 = 275 which is how many miles she drove in January.
275*4= 1100 which is how many miles she drove in February.
Ms. Turner drove 1100 miles in February.